Polis : an introduction to the ancient Greek city-state - Hansen, Mogens Herman, 1940- (Oxford University Press, 2006)
An accessible introduction to the polis (plural: poleis), or ancient Greek city-state. Mogens Herman Hansen addresses such topics as the emergence of the polis, its size and population, and its political culture, ranging from famous poleis such as Athens and Sparta through more than 1,000 known examples. - ;From antiquity until the nineteenth century, there have been two types of state: macro-states, each dotted with a number of cities, and regions broken up into city-states, each consisting of an urban centre and its hinterland. A region settled with interacting city-states constituted a city.